First signs of gentrification? Urban regeneration in the transitional society: the case of Croatia - Čaldarović, Ognjen (Array, 2008)
Gentrification as a narrow concept of urban regeneration is discussed. It is shown that instead of complex urban regeneration, gentrification as a proces of social change is taking place. The example discussed is the Flower Square in Zagreb